Pengetahuan Maskne Saat Pandemi Covid-19 pada Siswa-Siswi Kelas X SMA Kalam Kudus - Catharina Sagita Moniaga; Anggita Tamaro; Alicia Sarijuwita; Jasmine Syabania Noviantri (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2023)
During the Covid-19 pandemic, facial dermatitis namely acne due to masks (maskne), is well-recognized.. This disorder arises due to long-term use of masks, and leads to acne eruption. Maskne often occurs in society and the medical community, especially in the young age group. Wearing a mask can cause humidity and high skin temperature, which allows the growth of acne-causing bacteria, increased sweating, and continuous friction of the skin with the mask, which triggers the appearance of a maskne. Therefore, a good understanding of maskne, especially among adolescents, needs to be addressed and improved if necessary. The results of observations on Class X (Social Class) Kalam Kudus II Senior High School Jakarta showed that the understanding of maskne was not comprehensive. After the students received counseling about maskne, an increase in knowledge about maskne was obtained. This shows that knowledge about maskne as a type of disorder that emerged during the Covid-19 pandemic needs to be disseminated so that correct information can be obtained by the public.